CRISPR/Cas9 targeted inactivation of the kauniolide synthase in chicory results in accumulation of costunolide and its conjugates in taproots - Cankar, Katarina; Hakkert, Johanna Christina; Sevenier, Robert; Campo, Eva; Schipper, Bert; Papastolopoulou, Christina; Vahabi, Khabat; Tissier, Alain; Bundock, Paul; Bosch, Dirk (Frontiers in Plant Science, 2022)
Chicory taproots accumulate sesquiterpene lactones lactucin, lactucopicrin and 8-deoxylactucin, predominantly in their oxalated forms. The biosynthetic pathway for chicory sesquiterpene lactones has only partly been elucidated; the enzymes that convert farnesyl pyrophosphate to costunolide have been described. The next biosynthetic step of the conversion of costunolide to the tricyclic structure, guaianolide kauniolide, has so far not been elucidated in chicory. In this work three putative kauniolide synthase genes were identified in chicory named CiKLS1, CiKLS2 and CiKLS3. Their activity to convert costunolide to kauniolide was demonstrated in vitro using yeast microsome assays. Next, introduction of CRISPR/Cas9 reagents into chicory protoplasts was used to inactivate multiple chicory KLS genes and several chicory lines were successfully regenerated. The inactivation of the kauniolide synthase genes in chicory by the CRISPR/Cas9 approach resulted in interruption of the sesquiterpene lactone biosynthesis in chicory leaves and taproots. In chicory taproots, but not in leaves, accumulation of costunolide and its conjugates was observed to high levels, namely 1.5 mg/g FW. These results confirmed that all three genes contribute to STL accumulation, albeit to different extent. These observations demonstrate that three genes oriented in tandem on the chicory genome encode kauniolide synthases that initiate the conversion of costunolide towards the sesquiterpene lactones in chicory.